The Influence of Good Corporate Governance and Work Environment on Employee Performance with Work Engagement Mediation at Bank BRI Jayapura - Dasanti Jiwaning Winahyu; Indarto Indarto; Djoko Santoso (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the influence of good corporate governance and work environment on employee performance through work engagement. This study uses an explanatory research type, namely explaining the influence between certain variables through hypothesis testing. The population of this study was 152 employees of Bank BRI Regional Office Jayapura, with a convenience sampling method. The sample was taken based on the Slovin formula of 61 employees. The method of data collection in a scientific study is intended to obtain relevant, accurate, and reliable materials; the data collection method used in this study is a questionnaire. The results of the study indicate that good corporate governance and work environment have an effect on work engagement. Good corporate governance, work environment, and work engagement have an effect on employee performance. And good corporate governance and work environment have an effect on employee performance through work engagement.